2015
DOI: 10.3892/ol.2015.2988
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol inhibits the hedgehog signaling pathway and epithelial-mesenchymal transition and suppresses gastric cancer invasion and metastasis

Abstract: Abstract. The hedgehog (Hh) signaling pathway is vital to vertebrate development, the homeostatic process and tumorigenesis. Epithelial-mesenchymal transition (EMT) is a cellular process during which epithelial cells become mesenchymal-appearing cells, which in turn promotes cancer metastasis and invasion. Resveratrol is a natural polyphenolic compound found in grapes, a variety of berries, peanuts and other plants. Numerous studies have demonstrated that the Hh signaling pathway is able to regulate the EMT, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 52 publications
2
54
0
Order By: Relevance
“…Furthermore, it has previously been confirmed that resveratrol exerts antiproliferative and/or apoptotic effects on leukemia, prostate, breast and colon cancers cells in vitro (9)(10)(11)(12). Previous studies regarding the anticancer effects of resveratrol have focused on its anti-invasive and anti-metastatic activities (13)(14)(15). However, to the best of our knowledge, there is currently no evidence as to whether resveratrol may inhibit the migration and invasion of human bladder cancer cells.…”
Section: Introductionmentioning
confidence: 74%
“…Furthermore, it has previously been confirmed that resveratrol exerts antiproliferative and/or apoptotic effects on leukemia, prostate, breast and colon cancers cells in vitro (9)(10)(11)(12). Previous studies regarding the anticancer effects of resveratrol have focused on its anti-invasive and anti-metastatic activities (13)(14)(15). However, to the best of our knowledge, there is currently no evidence as to whether resveratrol may inhibit the migration and invasion of human bladder cancer cells.…”
Section: Introductionmentioning
confidence: 74%
“…In GC, tumorigenicity and EMT are regulated through activation of glioma-associated oncogene 1 (Gli1), a key member of the Hh signaling pathway [1315]. Hh signaling during embryogenesis promotes tissue growth, tissue patterning, vascularization, and differentiation, all of which are processes that tumor cells employ in order to support tumor growth and facilitate metastasis [11].…”
Section: Introductionmentioning
confidence: 99%
“…Gao and colleagues also demonstrated the anti-metastatic activity of resveratrol against gastric cancer cells by modulation of the Hedgehog signaling pathway through downregulation of Gli-1 expression. Moreover, resveratrol upregulated the expression of E-cadherin gene, decrease Snail protein and N-cadherin expression [234]. …”
Section: Metastasismentioning
confidence: 99%